Gambaran Kualitas Fungsi Penglihatan Pasien Systemic Lupus Erythematosus Berdasarkan Kuesioner NEI VFQ-25 Di Komunitas Odapus Lampung - Firhat Esfandiari; Festy Ladyani Mustofa; Rina Kriswiastiny; Dianing Ayu Yustika Ratu (Universitas Malahayati, 2021)
ABSTRACT: DESCRIPTION OF THE QUALITY OF VISION FUNCTION IN SYSTEMIC LUPUS ERYTHEMA PATIENTS BASED ON THE NEI VFQ-25 QUESTIONNAIRE IN THE ODAPUS COMMUNITY OF LAMPUNGBackground: Systemic Lupus Erythematosus /Systemic Lupus Erythematosus (SLE) is a multisystem autoimmune disease that has characteristic manifestations or symptoms and varied clinical behavior. Eye involvement can be found in about one-third of cases of SLE, and sometimes occurs early in the disease. To assess and measure the quality of vision function in patients with Systemic Lupus Erythematosus, a measuring instrument that can be used is the National Eye Institute Visual Functioning Questionnaire-25 (NEI VFQ-25) questionnaire. Objective: To describe the quality of vision function in patients with systemic lupus erythematosus based on the NEI VFQ-25 questionnaire in the ODAPUS community in Lampung 2020. Research Methods: This research is a descriptive survey with an approach cross-sectional using primary data in the form of a questionnaire. The sample of this study was all 40 patients who joined the ODAPUS community in Lampung. Data analysis used univariate analysis using tables and graphs in data presentation. Results: The results of the study were 40 patients who met the criteria for inclusion in the study. Of the 40 patients, the patient characteristics were obtained based on the quality of vision function, namely 26-45 years (65.0%), female (97.5%), tertiary education (65.0 %), IRT (42.5%), quality of vision function is not good (90 , 0%), low-dose corticosteroids (85.0%). Conclusion: Given picture quality visual functions of patients with systemic lupus erythematosus-based questionnaire NEI VFQ-25 in the community of Lampung odapus 2020 is not good. Keywords: Quality Vision Function, SLE INTISARI: GAMBARAN KUALITAS FUNGSI PENGLIHATAN PASIEN SYSTEMIC LUPUS ERYTHEMATOSUS BERDASARKAN KUESIONER NEI VFQ-25 DI KOMUNITAS ODAPUS LAMPUNG Latar Belakang: Lupus Eritematosus Sistemic/Systemic Lupus Erythematosus (SLE) adalah suatu penyakit autoimun multisistem yang memiliki manifestasi atau gejala khas dan perilaku klinis yang sangat bervariasi. Keterlibatan mata dapat ditemukan pada kurang lebih satu per tiga kasus SLE, dan kadang terjadi pada awal penyakit. Untuk menilai dan mengukur kualitas fungsi penglihatan pada pasien Systemic Lupus Erythematosus, alat ukur yang dapat digunakan yaitu dengan kuesioner National Eye Institute Visual Functioning Questionnaire-25 (NEI VFQ-25).Tujuan: Untuk mengetahui gambaran kualitas fungsi penglihatan pasien systemic lupus erythematosus berdasarkan kuesioner NEI VFQ-25 di komunitas ODAPUS Lampung 2020.Metode Penelitian: Jenis penelitian ini adalah survei deskriptif dengan pendekatan Cross- sectional menggunakan data primer berupa kuesioner. Sampel penelitian ini adalah seluruh pasien yang bergabung di komunitas ODAPUS Lampung sebanyak 40 orang. Analisis data menggunakan analisis univariat dengan menggunakan tabel dan grafik dalam penyajian data.Hasil: Hasil penelitian terdapat 40 pasien yang memenuhi kriteria untuk dimasukkan dalam penelitian. Dari 40 pasien tersebut didapatkan karakteristik pasien berdasarkan kualitas fungsi penglihatan yaitu terbanyak pada usia 26-45 tahun (65,0%), jenis kelamin perempuan (97,5%), pendidikan perguruan tinggi (65,0%), pekerjaan IRT (42,5%), kualitas fungsi penglihatan tidak baik (90,0%), dan penggunaan kortikosteroid dosis rendah (85,0%). Kesimpulan: Gambaran kualitas fungsi penglihatan pasien systemic lupus erythematosus berdasarkan kuesioner NEI VFQ-25 di komunitas ODAPUS Lampung 2020 yaitu tidak baik. Kata Kunci : Kualitas Fungsi Penglihatan, SLE